2014
DOI: 10.1088/0957-4484/25/4/045101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salts, solvents and buffer on miRNA detection using DNA silver nanocluster (DNA/AgNCs) probes

Abstract: MicroRNAs (miRNAs) are small regulatory RNAs (size ~21 nt to ~25 nt) which regulate a variety of important cellular events in plants, animals and single cell eukaryotes. Especially because of their use in diagnostics of human diseases, efforts have been directed towards the invention of a rapid, simple and sequence selective detection method for miRNAs. Recently, we reported an innovative method for the determination of miRNA levels using the red fluorescent properties of DNA/silver nanoclusters (DNA/AgNCs). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…To generalize the DNA/AgNC-based method, we further investigated the mechanism underlying the emission of strong fluorescence and optimized it under buffer conditions. 38,39 Furthermore, we showed that multiplex detection of miRNAs in solution is highly feasible using different DNA/AgNC sensors with different emission spectra. 40 In fact, we demonstrated that the method is practical enough for screening a novel mutant plant, whose miRNA biogenesis pathway is notably compromised or disrupted.…”
Section: Introductionmentioning
confidence: 96%
“…To generalize the DNA/AgNC-based method, we further investigated the mechanism underlying the emission of strong fluorescence and optimized it under buffer conditions. 38,39 Furthermore, we showed that multiplex detection of miRNAs in solution is highly feasible using different DNA/AgNC sensors with different emission spectra. 40 In fact, we demonstrated that the method is practical enough for screening a novel mutant plant, whose miRNA biogenesis pathway is notably compromised or disrupted.…”
Section: Introductionmentioning
confidence: 96%
“…The use of DNA template has the advantage of achieving specific target recognition through the direct incorporation of complementary DNA or aptamer sequences without the need for post-synthesis functionalization ( 37–40 ). There has been increased understanding on how the structure of AgNC correlates to its fluorescence properties ( 41–45 ); though for AgNC–DNA to truly take off as a toolbox for biomedical applications, the next technical hurdle is to generate DNA sequences for templating AgNC–DNA with good stability particularly in a chloride-rich environment ( 46 ). Some strategies were previously proposed to enhance the stability of AgNC–DNA, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to this, certain salts such as chloride ions have also been reported to interfere with AgNC formation when present at high concentrations. 59 Chloride ions have been shown to obstruct the formation of AgNCs via AgCl precipitation or the sequestering of silver ions. 59 Hence, chloride ions were replaced with nitrate ions in the preparation of Buffer A and Buffer B for the assay to avoid such issues.…”
Section: Resultsmentioning
confidence: 99%